Bone mineral density in patients with Parkinson's disease - Ardicoglu, O; Kamanli, A; Ozgocmen, S; Yoldas, TK (Springer London Ltd, 2004)
[Abstract Not Available]
IOF World Congress on Osteoporosis -- MAY 14-18, 2004 -- Rio de Janeiro, BRAZIL